DALIA MOGAHED’S IDENTITY AS REFLECTED IN TED TALKS VIDEO - Zaenul Kurniawan Syahid (English Letter Department, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
This study discussed the identity of Dalia Mogahed reflected through speech in an event called TED Talks. It is a big program have been featured great people around the world including Dalia Mogahed from various backgrounds to spread ideas. Her 2016 TED Talks entitled